Comparison of Berman and Ovassapian Intubating airways for fiberoptic orotracheal intubation in anaesthetized patient - Rajbanshi, Lalit Kumar; Singh, Satyendra Narayan (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: Intubating oral airways are widely used during fibreoptic orotracheal intubationin order to improve the bronchoscopic visualisation of the glottis and facilitate the procedure. This study compares the visualisation of the glottic opening with bronchoscope using Berman or Ovassapian intubating airway. Methods: We conducted a randomised comparative prospective study one hundred twenty patients with no clinical indicators of the difficult airway. The two oral intubating Berman and Ovassapian airways were compared during fibreoptic endotracheal intubation in anaesthetized patients. The bronchoscopic view, bronchoscopic time, and the total time for intubation were compared. Result: The bronchoscopic view was significantly better with Berman intubating airway (unobstructed view 74%) as compared to the Ovassapian airway (unobstructed 38.4%) (p-value 0.002). The Berman airway provided a significantly shorter duration for visualisation of the vocal cord and intubation of trachea in comparison to the Ovassapian airway. Conclusion: Berman airway provided a better bronchoscopic view as well as shorter bronchoscopic and intubation time as compared to the Ovassapian airway.